2008
DOI: 10.1128/aac.00902-07
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Genomic Island 1 (SGI1), Variant SGI1-I, and New Variant SGI1-O in Proteus mirabilis Clinical and Food Isolates from China

Abstract: Salmonella genomic island 1 (SGI1) and variants (SGI1-I and the new variant SGI1-O) were mapped in five strains of Proteus mirabilis isolated from humans and food in China. Sequencing showed that SGI1 and variants were integrated at the 3′ end of the chromosomal thdF gene as previously described for Salmonella strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…SGI1 can be mobilized by an IncC plasmid (13), and consistent with such horizontal gene transfer, SGI1 or variants of it have also been found in several other S. enterica serovars, including serovars Agona, Albany, Cerro, Derby, Dusseldorf, Infantis, Kentucky, Kiambu, Meleagredis, Newport, Paratyphi B dT ϩ , and Tallahassee (2, 4, 15-17, 22-24, 27, 40). Recently, SGI1 variants have also been found in Proteus mirabilis (1,6).…”
mentioning
confidence: 99%
“…SGI1 can be mobilized by an IncC plasmid (13), and consistent with such horizontal gene transfer, SGI1 or variants of it have also been found in several other S. enterica serovars, including serovars Agona, Albany, Cerro, Derby, Dusseldorf, Infantis, Kentucky, Kiambu, Meleagredis, Newport, Paratyphi B dT ϩ , and Tallahassee (2, 4, 15-17, 22-24, 27, 40). Recently, SGI1 variants have also been found in Proteus mirabilis (1,6).…”
mentioning
confidence: 99%
“…Moreover, three of them (isolates [12][13][14] exhibited the profiles of resistance to six antibiotic classes, closely resembling the aforementioned penta-resistance profile, typical of S. Typhimurium DT104. The differences were observed in resistance to one antibiotic ( …”
Section: Resultsmentioning
confidence: 99%
“…SGI1 is an integrative mobilizable element (IME), which can be transferred horizontally to other serotypes [9,10]. The different types of SGI1 MDR complex integrons have been described in a wide variety of S. enterica serotypes [11][12][13]18]. …”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that the mobilization of SGI1 probably contributes to the spread of antibiotic resistance genes between S. enterica serovars and possibly to other bacterial pathogens (Doublet et al, 2005). As predicted by Doublet et al (2005), a variant of SGI1 has been reported in Proteus mirabilis (Boyd et al, 2008). Moreover, a recent report showing the ability of IncA/C plasmids to mobilize SGI1 has implications for the worldwide spread of these MDR elements (Douard et al, 2010).…”
Section: Salmonella Genomic Islandmentioning
confidence: 96%